TREATMENT OF A CEREBRAL DISSECTING ANEURYSM IN ANTERIOR CIRCULATION: REPORT OF 11 SUBARACHNOID HEMORRHAGE CASES - OYAMA, HIROFUMI (Nagoya J Med Sci, 2012)
This report presents 8 cases of internal carotid artery aneurysms, 1 case of a middle cerebral artery aneurysm, and 2 cases of anterior cerebral artery aneurysms, together with a discussion of the treatment of aneurysms in anterior circulation. All cases showed subarachnoid hemorrhage. Two of the 8 internal carotid artery aneurysms were trapped with a low-flow bypass; however, both patients died of an immediate hemodynamic infarction or vasospasm-induced infarction. Five of the 8 internal carotid artery aneurysms were trapped after revascularization with high flow bypass. Four of those patients were self-supporting at discharge, but one patient was discharged in a vegetative state due to the sacrifice of arterial branches which were included in the dissecting portion. One case of the dissecting aneurysm in the M2 portion of the middle cerebral artery was trapped after low-flow bypass. This patient was self-supporting at discharge. In 2 cases of anterior cerebral artery aneurysms, the lesions were first wrapped with Bemsheets, and then the aneurysmal clip was applied on the wrapped dome. Trapping following high-flow bypass is the best method for treating a dissecting aneurysm in the internal carotid artery. Trapping also can be used to treat a dissecting aneurysm of the middle cerebral artery, after low-flow bypass. Clipping on the wrapped aneurysm can also be performed successfully in the anterior cerebral artery aneurysm.